Counseling Teacher Quality Improvement: Upaya Meningkatkan Kualitas Hubungan Siswa dan Guru - Neila Ramdhani; Yuliardi Swasono (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This article encompasses two studies about the influence of Counseling Teacher Quality Improvement (CTQI) Program in improving the competence of guidance and counseling teacher. The first study evaluated the effectiveness of CTQI in changing students and headmaster’s perceptions toward the way guidance and counseling teacher facilitates students in managing their problems. The second study aimed to examine the increase of guidance and counseling teacher’s counseling self-efficacy after participating in the three months counseling assistance program. Participants were 59 guidance and counseling teachers, 59 student groups, and 59 headmasters. Guidance and counseling teacher’s self-perception scale was given to teachers, perception toward teacher scale was given to headmasters and students. Counseling self-efficacy scale was only given to teachers. Data analysis showed that the perception of teachers, headmasters, and students increased after teachers partook in CTQI. Improvement also occured in counseling self-efficacy after counseling assistance program. However, headmasters’ perception toward guidance and counseling teachers’ counseling self-efficacy remained unchanged.